KAJIAN TEOLOGI HINDU DALAM TEKS SIWA TATTWA - I Wayan Sunampan Putra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Hinduism is a religion that has the concept of God that knows one God and pervades all things commonly called monotheism which is phantaism, which is a religion that believes in the existence of one Almighty God and permeates everything that exists so that what is not lahin is God itself. Likewise the concept of God in Shiva Tattwa's text shows a monistic teaching, that is, everything comes from God. The concept of belief in God Almighty is contained in the Vedic scriptures. The Vedas as a holy book is the main source of the teachings of Hinduism. Theology is basically the study of God, which in Hinduism is called Brahmawidya.